2022
DOI: 10.1002/ajh.26461
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 overexpression correlates with JAK2‐V617F mutational burden and is associated with 9p uniparental disomy in myeloproliferative neoplasms

Abstract: Myeloproliferative neoplasms (MPN) are chronic stem cell disorders characterized by enhanced proliferation of myeloid cells, immune deregulation, and drug resistance. JAK2 somatic mutations drive the disease in 50–60% and CALR mutations in 25–30% of cases. Published data suggest that JAK2‐V617F‐mutated MPN cells express the resistance‐related checkpoint PD‐L1. By applying RNA‐sequencing on granulocytes of 113 MPN patients, we demonstrate that PD‐L1 expression is highest among polycythemia vera patients and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Some of these antigens, such as CD99, CD117, CD123, CD184, and CD274 were found to be expressed at higher levels on MPN NSC compared to HSC in most donors, confirming the neoplastic nature of cells. With regard to CD274 (PD‐L1) these data confirm our previous observations 52 . Whether this excess in target expression would provide a therapeutic window remains unknown.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Some of these antigens, such as CD99, CD117, CD123, CD184, and CD274 were found to be expressed at higher levels on MPN NSC compared to HSC in most donors, confirming the neoplastic nature of cells. With regard to CD274 (PD‐L1) these data confirm our previous observations 52 . Whether this excess in target expression would provide a therapeutic window remains unknown.…”
Section: Discussionsupporting
confidence: 88%
“…So far, little is known about the phenotype of NSC in patients with MPN 51,52 . In the present study, we found that CD34 + /CD38 − MPN NSC display numerous 'therapeutic' targets, including CD33, CD44, CD47, CD97, CD99, CD117, CD123, CD133, CD184, and CD274 (PD‐L1) independent of the type of MPN or molecular driver lesion.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations